KINEMATIC CALCULATION AND SIMULATION OF THE PIERCING IN PIPE PRODUCTION - V. A. Tamila (Литьë и металлургия)
Computer model for simulating piercing process of steel workpiece was developed. Using finite element method the results obtained appropriate to the actual process with a high degree of accuracy. These results can be used when configuring the piercing mills, as well as piercing process optimization.